Sidelobe reduction with a GaN active array antenna. Issue 2 (21st November 2017) - Hasegawa, Naoki; Shinohara, Naoki
Abstract : This work proposes a tunable sidelobe reduction method based on a GaN active-antenna technique, in which the output radio frequency power is controlled by the DC drain voltage of the amplifiers. In this study, a 1 × 4 array of active antenna with GaN amplifiers is designed and fabricated. GaN amplifiers capable of up to 10 W-class power output are fabricated and arranged for a four-way active-array antenna. The fabricated single-stage GaN amplifier offers a maximum power-added efficiency of 59.6% and a maximum output power of 39.3 dBm. The maximum output power is decreased to 36.5 dBm upon decreasing the operating drain voltage from 55 to 35 V. In this study, a 4.5 dB sidelobe reduction is demonstrated in a 1 × 4 active antenna based on this output power difference for each amplifier.